Tetraneuraulmi Linnaeus, 1758 (Homoptera, Aphididae) on elm (Ulmus pumila)as its primary pest (Mongolian Journal of Agricultural Sciences, 2015)
The aphid Tetraneura ulmi causes a fig like gall to be formed on certain species of elm. T. ulmi is widely distributed Euro-Asian species which was secondarily introduced into North America. It attacks numerous species of elm. In Mongolia particularly Ulmus pumilla. The research was carried out in 2014 in the garden field (J. Sambuu named after the street, S. Zorig garden ) city of Ulaanbaatar. The observations were concerned with Ulmus pumila that grow in the garden that is located in the city centre.Journal of agricultural sciences №15 (02): 143-146, 2015